Foreign Exchange Rate Futures Trends: Foreign Exchange Risk or Systematic Forecasting Errors? - Marcelo Cunha Medeiros; Márcio G. P. Garcia; Daniel Chrity (Revista Brasileira de Finanças, 2006)
The forward exchange rate is widely used in international finance whenever the analysis of the expected depreciation is needed. It is also used to identify currency risk premium. The difference between the spot rate and the forward rate is supposed to be a predictor of the future movements of the spot rate. This prediction is hardly precise. The fact that the forward rate is a biased predictor of the future change in the spot rate can be attributed to a currency risk premium. The bias can also be attributed to systematic errors of the future depreciation of the currency. This paper analyzes the nature of the risk premium and of the prediction errors in using the forward rate. It will look into the efficiency and rationality of the futures market in Brazil from April 1995 to December 1998, a period of controled exchange rates.